Pengaruh Efikasi Diri dan Kompetensi Kewirausahaan terhadap Keberhasilan Usaha (Studi pada Usaha Mikro Kuliner di Banjarmasin Selatan) - Fitria Amelia amelia; Anna Nur Faidah (Universitas Lambung Mangkurat, 2025)
This research aims to determine and analyze: (1) The influence of self-efficacy on business success in culinary micro-enterprises in South Banjarmasin District; and (2) The influence of entrepreneurial competence on business success in culinary micro businesses in South Banjarmasin District. The type of research used in this research is quantitative research using survey methods. The total sample was 50 respondents. The sampling technique used was purposive sampling. The data collection technique uses a questionnaire and the data analysis technique used in this research is multiple linear regression analysis. The results of this research show that self-efficacy has a positive and significant effect on business success in culinary micro businesses in South Banjarmasin District. Entrepreneurial Competence has a positive and significant effect on the success of culinary micro businesses in South Banjarmasin District.